Evaluation of the potencial productivity of the black sorghum to forage (Sorghum almum). - Araya, Eugenio (2016)
Information on productivity and nutritional composition of forage black sorghum or Columbus grass (Sorghum almum) was obtained though five cuts, 63 days long each one. The first cut was in October - November 1991, the second in December 1991 - January 1992, the third in February - March 1992. A second set of cut took place with the fourth cut in September - October 1992 and the fifth in November - December 1992. The variables evaluated were Neutral Detergent Fibrous (FND), Dry Matter (MS), Dry Forage by Hectarea (FSH) and Crude Protein (PC), but only FSH, MS and FND tumed to be significantly important (P<0,01).